Investigating the effect of implementing continuous care model on fatigue and quality of life of patients with COVID-19 disease - Maryam Rezaee; Rahimali Shaikhy; Hadi Raeesi-Shahraki; Hedayat Allah Lalegani; Masood Hafizi-Isfahani; Shirmohammad Davoodvand (Journal of Multidisciplinary Care)
Background and aims: Chronic fatigue and decreased quality of life are complications of COVID-19. This study aimed to determine the impact of the continuous care model implementation on fatigue and quality of life of patients with COVID-19. Methods: This semi-experimental study was conducted with pre-test and post-test design in Shahrekord, Iran, 2022. The study was conducted on 80 patients with COVID-19 who were hospitalized at Hajer hospital in Shahrekord and Seyed al-Shohda hospital in Farsan. They entered the study by convenient sampling and were randomly assigned to intervention and control groups using cards. The continuous care model was implemented in 4 stages for the intervention group for three months. Data were gathered using the demographic data questionnaire, Krupp et al.’s fatigue intensity questionnaire (1989), and St. George’s Quality of Life Questionnaire (SGRQ) (1991), then analyzed with SPSS19 software. Results: Before the intervention, both groups had no statistically significant difference between fatigue intensity (P=0.65) and quality of life (P=0.47). The fatigue intensity immediately after the intervention and three months later in the intervention group was significantly lower than in the control group (P<0.001). The quality of life immediately after the intervention and three months later in the intervention group was significantly higher than the control group (P<0.001). Conclusion: Considering the effectiveness of the continuous care model in COVID-19 complications, it is recommended that healthcare professionals train and use it to take care of these patients and in similar cases.